USM Mini Remotely Operated Vehicle: Vehicle Development & Integration. - Mohd Yusoff, Mohd Akmal; Arshad, Mohd Rizal (Universiti Sains Malaysia, 2008)
This paper describes the development of vehicle design and hardware integration of the Mini remotely Operated Vehicle developed by members of USM Robotics Research Group.